Healable Thermoplastic for Kinesthetic Feedback in Wearable Haptic Devices - Carpenter, Cody W. (Sens Actuators A Phys, 2019)
The word “haptics” refers to technologies designed to stimulate the tactile and kinesthetic senses. Kinesthesia—the sense of motion—is triggered by imposing forces upon the joints, tendons, and muscles to recreate the geometry and stiffness of objects, as may be useful in physical therapy or virtual reality. Here, we introduce a form of kinesthetic feedback by manipulating the mechanical properties of spandex impregnated with a thermoplastic polymer. Heating or cooling this textile-thermoplastic composite just above or below its glass transition temperature (T(g)) dramatically changes its mechanical properties (corresponding to a decrease in storage modulus from 36 MPa to 0.55 MPa). In the form of a glove, the composite can also be healed after inadvertent overextension in its stiffened state by heating it above its T(g). When fitted with thermoelectric devices for active heating and cooling, the flexible or stiffened state of a glove can be perceived by human subjects. As an example of a human-machine interface, the glove is used to control a robotic finger. When the robotic finger makes contact with a wall, a signal is sent to thermoelectric devices in the glove to cool (stiffen the finger) and thus provide kinesthetic feedback to the user.